Digital Technologies in Distance Pedagogy and Psychocorrection during COVID-19 Pandemic - A. V. Solodukhin; D. A. Sidorckin (СибСкрипт)
This review presents a comprehensive analysis of theoretical and experimental studies of digital technologies in pedagogy and psychocorrection during the COVID-19 pandemic. The remote digital format demonstrated a number of limitations and disadvantages, i.e., technical and organizational problems. However, digital technologies made it possible to provide academic and psychological services to a wide range of population, regardless of the social, education, and financial status. The following recommendations could improve the distance pedagogical and psychocorrective services in pandemic environment: emphasis on specific academic and psychotherapeutic goals and tasks; a mandatory mental health monitoring system, e.g., online surveys and questionnaires; a unified scientific and evidence-based concept, e. g., a cognitive behavioral approach. The Aita software demonstrated good prospects as a platform for psychological and pedagogical services to former COVID-19 patients or survivors of other serious neuroinfectious diseases.